1990
DOI: 10.1523/jneurosci.10-12-03992.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cell interactions regulate dendritic morphology and responses to neurotransmitters in embryonic chick sympathetic preganglionic neurons in vitro

Abstract: The influence of non-neuronal cells and interneurons on the morphological development of chick sympathetic preganglionic neurons (SPNs) and on the responsiveness of these neurons to the neurotransmitters GABA, glycine, and glutamate was studied. SPNs were retrogradely labeled with the fluorescent dyes dil and diO, then separated from spinal-cord non-neuronal cells and interneurons by fluorescence-activated cell sorting. SPNs were grown in culture, either alone or in coculture with non-neuronal cells alone, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The mechanism by which the satellite cells operate has not been determined. Interestingly, this satellite cell influence on sensory neurons is opposite to the influence of glial cells on neurons that normally extend dendrites in vivo (Tropea et al, 1988;Johnson et al, 1989;Clendening and Hume, 1990); in these latter studies, the presence of glial cells induces dendrite outgrowth. Therefore, with respect to dendrites, these results suggest that, in culture, glial cells influence neurons to acquire properties that they would normally have in vivo.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanism by which the satellite cells operate has not been determined. Interestingly, this satellite cell influence on sensory neurons is opposite to the influence of glial cells on neurons that normally extend dendrites in vivo (Tropea et al, 1988;Johnson et al, 1989;Clendening and Hume, 1990); in these latter studies, the presence of glial cells induces dendrite outgrowth. Therefore, with respect to dendrites, these results suggest that, in culture, glial cells influence neurons to acquire properties that they would normally have in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have indicated that the initiation of dendrites is, in part, governed by mechanisms intrinsic to neurons (Dotti et al, 1988;Black and Baas, 1989). In addition, there is ample evidence that extrinsic factors influence neuronal polarity and dendritic arborization (Mudge, 1984;Bruckenstein and Higgins, 1988a,b;Purves et al, 1988;Snider, 1988;Tropea et al, 1988;Chamak and Prochiantz, 1989;Johnson et al, 1989;Lein and Higgins, 1989;Clendening and Hume, 1990;&hilling et al, 1991).…”
mentioning
confidence: 99%
“…Multiple previous studies have also reported the expression of differential neurotransmitter and receptor properties by neurons, depending on neuronal surroundings (Clendening and Hume, 1990;Paschen et al, 1997), depolarization, specific neurotransmitters (Patterson, 1978), target tissue interactions (Landis, 1990), glial-neuronal communication (Poulter andBrown, 1999), hormones (McCauley andGee, 1995;Zhang et al, 1999), and neurotrophins (Ernsberger and Rohrer, 1988;Iacovitti et al, 1989;Sieber-Blum, 1991).…”
Section: Differentiation Of Transplanted Neuroblasts To a Mature Cpn mentioning
confidence: 97%
“…Changes in the response to neurotransmitters can also arise through serial acquisition of sensitivities to more than one transmitter during the course of differentiation, leading to a change in the aggregate response. This process can be regulated postsynaptically, by serial appearance of receptors for different ligands (Clendening and Hume, 1990a), and influenced by the presence of nonneural cells as well as other neurons (Clendening and Hume, 1990b). It may also be regulated presynaptically, by sequential appearance of two or more cotransmitters in other cases.…”
Section: Neurotransmitter Sensitivitymentioning
confidence: 99%